Extracellular matrix and the liver : approach to gene therapy - Okazaki, Isao (Academic Press, 2003)
Extracellular Matrix of the Liver addresses the basic science of the extracellular matrix and discusses new strategies for the treatment of cirrhosis of the liver, with a primary focus on possible gene therapy approaches. The chapters are divided into six sections as follows: * Basic Science of Extracellular Matrix * Cells Responsible for Extracellular Matrix Production * Activation Mechanism of Hepatic Cells and Signal Transduction * Basic Science for Extracellular Matrix Metabolism including Enzymes and their Inhibitors * Matrix Mettaloproteinases and Tissue Inhibitors for Matrix Mettaloproteinases * New Strategies for the treatment of Liver Cirrhosis Key Features * Discusses the possibility of gene therapy for liver cirrhosis * Includes information on new aspects of hepatic stellate cells * Written by top experts in basic science and clinical hepatology.